2017
DOI: 10.3233/bmr-169573
|View full text |Cite
|
Sign up to set email alerts
|

The immediate effects of manual stretching and cervicothoracic junction manipulation on cervical range of motion and upper trapezius pressure pain thresholds

Abstract: This study demonstrates the potential independent effectiveness of spinal thrust manipulation or stretching for reducing PPTs at the upper trapezius. Future research should further evaluate the limitation of PPTs as a measure of muscle sensitivity as well as factors that may contribute to variability in the measurements among individuals seeking care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 32 publications
5
17
2
Order By: Relevance
“…13 These¯ndings are in line with previous studies which concluded that stretching has shown improvement in PPT scores when performed alone or given with other treatment. 6,28 In this study, stretching showed an increase in the post-WBLT score which displayed statistical signi¯cance. This may be attributed to the viscoelastic properties of the musculotendinous unit to relax and lengthen.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…13 These¯ndings are in line with previous studies which concluded that stretching has shown improvement in PPT scores when performed alone or given with other treatment. 6,28 In this study, stretching showed an increase in the post-WBLT score which displayed statistical signi¯cance. This may be attributed to the viscoelastic properties of the musculotendinous unit to relax and lengthen.…”
Section: Discussionsupporting
confidence: 52%
“…These¯ndings are in line with a study which reported increased ROM after stretching. 28 In our study, foam rolling showed statistically signi¯cant di®erence in pain. These¯ndings may be attributed to biomechanical, physiological and neurological mechanisms.…”
Section: Discussionsupporting
confidence: 46%
“…n = 26Group 2: mobility group, prone segmental mobility test from T3-T8. n = 26Immediately post intervention.Thoracic spine (T3-T8) seated AROM (°) in forward bend, right & left side bend.Forward bending ROM:Control-Palpation: − 1.1 ° (− 2.50, 0.30)SMT-Control: 1.0° (− 0.47, 2.47)SMT-Palpation: − 0.1° (− 1.83, 1.63)Right-side bend ROM:Control-Palpation: − 0.3° (− 2.09, 1.49)SMT-Control: 1.5° (0.17, 3.17)SMT-Palpation: 1.2° (− 0.64, 3.04)Left-side bend ROM:Control-Palpation: − 0.7° (− 2.13, 0.73)SMT-Control: 2.2° (0.91, 3.49)SMT-Palpation: 1.5° (− 0.18, 3.18) Hanney et al, 2017 [39]Students, faculty or staff of University of Central Florida; 18–50 years; Florida, USA; n = 102; Randomized controlled trial.Bilateral cervicothoracic thrust manipulation. n = 34Manual stretching: supine with passive flexion, lateral flexion away and rotation of head towards stretched side until barrier was met for 30 s, 2x/side. n = 34No treatment: seated for 3–5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Manual therapy techniques have been well described in the literature over the years and date back well beyond the scope of this study [2][3][4][5][6][7][8][9][10][11][12]. The benefits of HVLA thrust techniques for spinal and extremity pain or dysfunction are widely recognized in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of HVLA thrust techniques for spinal and extremity pain or dysfunction are widely recognized in the literature. For example, reduction in pain and improved function following HVLA thrust manipulation to the cervicothoracic region has been widely reported in patients with neck pain and shoulder pain [2,[5][6][7]10]. Achieving isolated specific facet cavitation is not consistent with the literature when applying segment-specific HVLA techniques throughout the upper and lower cervical, cervicothoracic, thoracic, and lumbar spine regions [2][3]9].…”
Section: Introductionmentioning
confidence: 99%